Valerie Desmore s refusal(s): art practice as biomythography - Akoi-Jackson, Nontobeko Ntombela (Michaelis School of Fine Art, 2024)
The South African-born British artist and fashion designer Valerie Elizabeth Helene Desmore, who is said to have risen to fame in South Africa in 1942 at the age of sixteen, left South Africa in 1945 to pursue an art career in the United Kingdom. This move was prompted by the infamous South African race bar through which she experienced significant ‘racial persecution'. Feeling rejected, her exile in the United Kingdom resulted in a career change from visual arts to fashion, only to return to visual arts again in her senior years. This oscillation between visual art and fashion culminated in an idiosyncratic body of work that this thesis, through the concepts of refusal and biomythography, examines. This is done by analysing her artworks as they tell her life stories. Argued via a critical consideration of how the artist's work bears rich articulations of selfdetermination, self-writing, and self-enunciation in bold and unapologetic gestures, the dissertation shows patterns of a visual trajectory marked by a series of refusals and her own avant-garde style. Using ‘encumbered methodology' the thesis centres the artist's agency as well as her legacy, as prerequisites for any meaningful undertaking of art-historical writing. As such, the methodology and theoretical framework of refusal and biomythography combined illuminate a multitude of the artist's complex experiences, showing how significant multivocality has become in contemporary art historical practice. In turn, this further reveals how Desmore's choice to reciprocally reject (depart from) that which rejected her (denied her access) disrupted known workings of art historical exclusions. Desmore's audacious gestures complicate and refute the often-simplified understandings of Black South African Modern artists as passive participants and ‘discovered subjects' in the making of their careers. By examining the work of one woman artist, Valerie Desmore, this research asserts a renewed, gendered positionality for Black South African Modern women artists more broadly. The thesis, therefore, presents efforts to re-member and re-assemble the life and work of an artist nearly erased from the art historical canon. Drawing on Black feminist and postcolonial methodologies the thesis lays bare the challenges of researching invisible, disparate and undervalued archival and historical materials.